Visualizing Discrimination in Multimodal Discourse Analysis of Werewolf Marginalization in Days of Hana - Zahra, Banan Az; Saehu, Andang; Yatmikasari, Ika (English Language in Focus (ELIF), 2025)
This study aims at analyzing social issues like segregation and discrimination in the webtoon Days of Hana by Seokwoo, which tells a fictional story about humans and werewolves. This study uses Multimodal Discourse Analysis (MDA) following Kress and van Leeuwen’s Visual Grammar framework to look at how visual elements create meaning. The analysis uses a qualitative descriptive method to look at how discrimination against werewolves is represented through visual elements, including facial expressions, perspective angles, and image composition. The findings show that Days of Hana does a great job of using different modes to show social hierarchies and power dynamics, which adds depth to the story and really connects with readers emotionally. This study shows how webtoons serve as easy-to-access cultural media that can communicate important social messages.